Local authorities in Crete and the development of tourism - Andriotis, Konstantinos (My University, 2002)
It is widely accepted that local authorities play a significant role in the development of the tourism industry of islands by providing various services and infrastructure. This study reports on a survey of local authorities in the Greek island of Crete and has two main objectives: (i) to explore local authorities’ involvement in tourism and their activities to the tourism development of the island; and (ii) to elicit suggestions by local authority officials for the further tourism development of the island. The results indicate that although the variety of the actions currently undertaken by the local authorities, towards the tourism development of the island, there is still a need for more efforts to promote tourism and to provide more opportunities for encouraging tourism development. As a result, this paper discusses the implications of the findings for Cretan tourism and provides conclusions for the future tourism development of the island.